Ceremonie na ratuszu krakowskim w XV–XVIII wieku - Wyżga, Mateusz (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
Ceremonies at the town hall in Kraków from the 15th to 18th century (Summary) Sources with information on ceremonies at the town hall in Kraków are somewhat brief. Most of the information can be found in the ledgers. The status of capital gave the city considerable significance within the state. By organizing ceremonies at Kraków’s town hall, council elections, paying homage to kings, hosting senior state officials and deputies, the town authorities could influence politics. The Kraków town hall remained an important centre both for official celebrations and carnivalesque events. It was therefore an important place with regard to the policy of the municipal council until the end of the Polish Noble’s Republic. Here the town was able to overcome its limitations and defend its autonomy, both formally and informally impacting Poland’s elite. The participation of state officials in municipal ceremonies was an opportunity to show off the splendour of Kraków. This was particularly true after the transfer of the royal court to Warsaw, when the kings visited their temporary Wawel residence less frequently. The role of the town hall in social communication was twofold. On the one hand it was a form of promotion for the town, on the other it was a barrier between representatives of the authorities and the ordinary citizens of Kraków. The town hall was a cultural place and a sign of the exceptionally extroverted, developed collective life of the old town. The square in front of the town hall was also important. It was a typical municipal theatre. Ceremonies held in Kraków took the form of court and state ceremonies.